Electrodialysis as part of the integrated membrane process for landfill leachate treatment - Kulhavý, Michal; Cakl, Jiří; Václavík, Lukáš; Maršálek, Jiří (Taylor&Francis Inc, 2019)
Desalination of leachates from municipal and hazardous waste landfills using electrodialysis was studied experimentally. The process was integrated into the complex technology for leachate treatment to reduce the concentration of inorganic salts prior to the reverse osmosis (RO). The technology principle is as follows: electrodialysis minimizes osmotic pressure of RO feed, thus the process can be operated economically using low-pressure and fouling-resistant RO membranes and low salinity RO concentrate can be easily recycled back into the landfill body. The pilot batch electrodialysis experiments were carried out with several types of leachate wastewaters which were collected from two municipal waste landfills and one landfill for the disposal of hazardous waste. The results of the experiments demonstrate that the electrodialysis integrated into the treatment system allows the reduction of the dissolved solids content in the leachate to 18%-27% of the initial value. Most of the organic matter remains in the leachate (diluate) together with multivalent ions, especially Fe3+, Ba2+, Sr2+ and B3+. If the concentrate pH was kept as low as necessary to achieve Langelier saturation index below -0.2, then it was possible to realize the process with the minimum ratio of the concentrate to diluate volume. An effective method to recover the system from physical and chemical reversible fouling using alkaline cleaning in place was also found and verified.
Elektrodialýza jako součást integrovaného membránového procesu pro zpracování výluhu ze skládek
Keywords: electrodialysis; wastewater treatment; leachate; scaling; membrane fouling; elektrodialýza; čištění odpadních vod; skládkové výluhy; scaling; zanášení membrán